Relieving Depressive Symptoms Through Chinese Relational Culture Among Older Adults with Multimorbidity: Evidence from CHARLS - Duan XY; Sun T; Lu F; Yang XJ; Yin HY; Cao DP; Zhang SE (Psychology Research and Behavior Management)
Xin-Yu Duan,1 Tao Sun,2 Feng Lu,1 Xiao-Jing Yang,1 Hong-Yan Yin,3 De-Pin Cao,1,* Shu-E Zhang1,* 1Department of Health Management, School of Health Management, Harbin Medical University, Harbin, People’s Republic of China; 2Department of Health Policy and Management, School of Public Health, Hang Zhou Normal University, Harbin, People’s Republic of China; 3Department of Humanities and Social Sciences, Harbin Medical University (Daqing), Daqing, Heilongjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: De-Pin Cao; Shu-E Zhang, Department of Health Management, School of Health Management, Harbin Medical University, Harbin, 150081, People’s Republic of China, Tel +86 13351113008; +86 15104694354, Email caodp211@126.com; hydzhangshue@163.comBackground: Depressive symptoms and multimorbidity are global public health concerns, the relationship between the two variables remains unclear. This study was an intervention attempt through the lens of regional relational culture to identify and reduce adverse consequences of this relationship. We aimed to explore the prevalence of multimorbidity and depressive symptoms among older Chinese adults, the association between the two variables, and the underlying moderating mechanism.Methods: This study extracted data from the China Health Retirement Longitudinal Study (CHARLS) of 8356 older adults aged 60 years and older and analyzed the correlation between multimorbidity and depressive symptoms in this population using Stata 16.0. Moreover, the correlation between multimorbidity and depressive symptoms was verified using logistic regression analysis, and a hierarchical multiple regression analysis was used to test the existence of moderating effects between the two variables.Results: The prevalence of multimorbidity and depressive symptoms among seniors aged 60 years and older was 66.16 and 36.85%, respectively. Multimorbidity was positively associated with depressive symptoms (p< 0.001), and relationship satisfaction, social activity, and information isolation moderated this association (p < 0.05).Conclusion: Older adults with multimorbidity are more likely to develop depressive symptoms, and regional relational culture can play a moderating role between them. The government, as well as aging-related sectors, can reduce the risk of depressive symptoms by improving relationship satisfaction, increasing social activity, and decreasing information isolation among older adults.Keywords: depressive symptoms, multimorbidity, older adults, relationship satisfaction, social activity, information isolation